Are nurses more altruistic than real estate brokers? - Karin Jacobsen; Kari H. Eika; Leif Helland; Jo Thori Lind; Karine Nyborg (Institute for the Study of Labor (IZA), 2011)
We report results from a dictator game experiment with nurse students and real estate broker students as dictators, and Amnesty International as the recipient. Although brokers contributed substantial amounts, nurses contributed significantly more, on average 76 percent of their endowment. In a second part, subjects chose between a certain repetition of the experiment and a 50-50 chance of costly exit. About one third of the brokers and half of the nurses chose the exit option. While generosity was indeed higher among nurses, even when taking exits into account, the difference cannot readily be attributed to different degrees of altruism.
urn:nbn:de:101:1-201106013345
Keywords: D10; D64; 330; dictator game; exit option; generosity; occupational differences